Determinación del efecto de dos tipos de ceras naturales (carnauba y de abeja) para recubrimiento de banano (Musa acuminata) como medio de conservación - Zambrano Muñoz Denisse Margoth (2015)
This investigation seeks to establish the appropriate parameters for the banana tree conservation (Muse acuminata), by means of a covering with wax (Carnauba and bee wax), evaluating two type of these. Was the problem that ¨ was approached What it influences he/she would have the natural application of wax in the conservation of the banana tree? ¨ For what thought about as objective: To determine the effect of natural two types of waxes (carnauba and of bee) for banana tree covering (Muse acuminata) like half of conservation. Also thought about to determine which of the banana tree varieties Cavendish Williams or Banana tree Gold respond from a better way to two types of wax: carnauba and of bee, with two different concentrations (0.00%, 0.02% and 0.04%), with the purpose of prolonging the useful life of the same one. The experimental pattern allowed the application of a Design of Blocks with factorial Arrangement AxBxC with two replications that is to say 12 treatments with 2 repetitions giving a total of 24 experimental units. The factors in study were: as factor TO Varieties (Banana tree Cavendish Williams and Banana tree Gold), factor B Types wax (Carnauba and of Bee) and factor C Concentrations Zero (0.00%, 0.02% and 0.04%), for the separation of stockings of the levels of the treatments one went to the test of significance of TUKEY (p <0,05). The analysis of data was carried out by means of the statistical package StatGraphics. ...